2008
DOI: 10.1021/jp801274u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Position and Number of Positive Charges on the Intercalation and Stacking of Porphyrin to Poly[d(G-C)2], Poly[d(A-T)2], and Native DNA

Abstract: The effect of the number and position of the positive charges on porphyrin with respect to the mode of binding to poly[d(G-C)2] and poly[d(A-T)2] were investigated by absorption and polarized spectroscopy, including circular and linear dichroism (CD and LD). Meso-tetrakis(N-methylpyridinium-4-yl)porphyrin (TMPyP), which possesses four positive charges on the periphery pyridinium rings, produces a negative CD and wavelength-independent reduced LD (LDr) spectra in the Soret absorption region when it associates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…33, 34 The CD spectrum at these low BMPyP concentrations was extremely weak, as previously reported, 34 and therefore not shown. Polarized spectroscopic study suggested that BMPyP stacked along the stem of the DNA and poly[d(A-T) 2 ] and bound to the outside of poly[d(G-C) 2 ] in a monomeric manner.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…33, 34 The CD spectrum at these low BMPyP concentrations was extremely weak, as previously reported, 34 and therefore not shown. Polarized spectroscopic study suggested that BMPyP stacked along the stem of the DNA and poly[d(A-T) 2 ] and bound to the outside of poly[d(G-C) 2 ] in a monomeric manner.…”
Section: Resultssupporting
confidence: 49%
“…Polarized spectroscopic study suggested that BMPyP stacked along the stem of the DNA and poly[d(A-T) 2 ] and bound to the outside of poly[d(G-C) 2 ] in a monomeric manner. 34 The presence of ethidium did not alter the spectral properties of BMPyP bound to any of the polynucleotides, similar to TMPyP, suggesting that the simultaneous binding of BMPyP and ethidium to DNA and the synthetic polynucleotides did not affect their binding modes.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Differences in the binding geometries of the acceptors, TMPyP and BMPyP, resulted in different relative orientations. The binding modes of TMPyP and BMPyP to DNA and to selected synthetic polynucleotides has been investigated by polarized light spectroscopy, 34,35 with TMPyP found to intercalate between DNA base-pairs and BMPyP stackinf along the DNA stem. Therefore, their transition dipoles would be differently oriented relative to the DAPI.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Their different binding modes to DNA allow investigation of the effects of spectral overlap and relative orientation in RET. DAPI was used at a concentration ratio to DNA bases of 0.005, one DAPI molecule per 200 bases.…”
Section: -19mentioning
confidence: 99%